Properties of cement brick containing coconut husk fiber as partial sand replacement title - Muhammad Aizuddin, Mohammad (2017)
Coconut Husk Fiber can be use as material to increase the quality of concrete brick if used properly. This research is to investigate the properties of brick when coconut husk are mixed as material. The effect of the coconut husk fiber amount on the compressive strength, flexural strength and water absorption will be investigated in this research. Coconut fibre amongst all natural fibres is the most ductile. Coconut fibres have the capacity of taking strain 4-6 times more than that of other natural fibres. Sample with size 21Omm x 1OOmm x 65 mm were cast and tested at 7, 14 and 28 days. The sample consist of 0% (control), 2%, 4% and 6% coconut husk fiber content. There is an increase in compressive and flexural strenght for 4% and below percentage of coconut husk fiber. In conclusion, coconut husk fiber can be use as material to increase the quality of concrete brick.